DAMPAK INDEPENDENSI DAN PRODUK PERATURAN HUKUM KPK ATAS DIUNDANGKANNYA UNDANG-UNDANG NOMOR 19 TAHUN 2019 - Fransisca Haryono, Priskila; Yulia Rana Sinta Dewi, Elisabeth; De Marrilac Arianto, Louisa (The Juris, 2021)
Indonesia’s Corruption Eradication Commission is a Auxiliary State’s Organ that was born to help Main State’s Organ in trias politica by Montesqiue: the executive, the legislative and the judicial. KPK is independent, KPK’s independency is a delegation authority from 1945 Constitution of the Republic Indonesia. But, after the legitimate of Undang Undang No. 19 Tahun 2019 KPK entered into the executive clumps. In carrying out its duties, KPK released several legal products. The external legal products that released by the Main State’s Organ and the internal legal products that released by KPK itself. The existence of internal legal products of KPK are recognized and has permanent and binding legal force.